The Analisis Perilaku Bersosialisasi Anak Di Sekolah Dasar Ditinjau Dari Perbedaan Latar Belakang Keluarga - Salsabilah, Novalina; Putri Sakinah, Anastasia; Widya Anggraini, Tiara (Lembag, 2024)
All children are born in different environments and home environments. But one thing is certain: children need love and guidance to help them thrive in every aspect of their lives. Currently, there are many differences in children's family backgrounds that influence their socialization behavior. The reason behind this is because there are harmonious families, there are also broken homes. In the family, parents in particular play an important role in the development of a child's personality, especially in the child's daily behavior. The aim of this research is to describe children's social behavior when viewed from differences in family background. The research method used in this article is qualitative research, namely descriptive research in the form of describing/exposing the behavioral symptoms of people being observed. Researchers are the main instrument of research carried out at MI Al Awal Palembang for comprehensive data collection. This panel research was carried out in class IV at MI Al Awwal Palembang. The research results show that there are many differences in the social behavior of each child when viewed from family background. We identified two different family backgrounds, namely a harmonious family and a broken home family. So the solution that can be implemented in developing the character and social behavior of children who come from broken homes is that teachers must guide and educate children so that they can change their character from bad habits to good ones, they must try to understand children's feelings and provide advice and considerations as best as possible. Teachers must also try to bring children closer to their friends. The role of peers is no less important, because one of their roles is to provide a source of information and comparison about the world outside the family environment